2021
DOI: 10.1111/1346-8138.15928
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of intravenous injection of clonal mesenchymal stem cells derived from bone marrow in five adults with moderate to severe atopic dermatitis

Abstract: Atopic dermatitis is a chronic and relapsing inflammatory skin disease that is treated with immunosuppressants. However, long-term use of immunosuppressants may cause toxicity and severe side effects. To confirm the long-term efficacy and safety of clonal mesenchymal stem cell therapy, we performed investigator-initiated clinical trials and long-term observation in five adult patients with moderate to severe atopic dermatitis that was refractory to conventional treatments. The clinical response assessment valu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“… 96 Other 5 patients without ideal respondence to conventional treatments were administrated with 1.0 × 10 6 cells/kg MSCs intravenously and showed good clinical improvement in the follow-up. 97 Various studies with a larger number of patients, more reasonable grouping and MSC dose selection criteria are working together for clinical efficacy demonstration ( Table 4 ).…”
Section: Msc Therapy In Atopic Dermatitismentioning
confidence: 99%
“… 96 Other 5 patients without ideal respondence to conventional treatments were administrated with 1.0 × 10 6 cells/kg MSCs intravenously and showed good clinical improvement in the follow-up. 97 Various studies with a larger number of patients, more reasonable grouping and MSC dose selection criteria are working together for clinical efficacy demonstration ( Table 4 ).…”
Section: Msc Therapy In Atopic Dermatitismentioning
confidence: 99%
“…They found that the Eczema Area and Severity Index (EASI) improved significantly at 16 weeks, which had a long-term efficacy for an average of 38 weeks (range, 16–86), whereas it showed no serious side effects in the patients. Moreover, the pro-inflammatory cytokines in their blood significantly decreased at the end point ( 28 ). Similarly, Kim et al.…”
Section: The Clinical Efficacy Of Mscs and Their Derivatives Applied ...mentioning
confidence: 99%
“…They found that the Eczema Area and Severity Index (EASI) improved significantly at 16 weeks, which had a longterm efficacy for an average of 38 weeks (range, 16-86), whereas it showed no serious side effects in the patients. Moreover, the proinflammatory cytokines in their blood significantly decreased at the end point (28). Similarly, Kim et al recruited 34 patients with moderate-to-severe AD with a follow-up for 1 and 3 months revealed that subcutaneously administering a high dose of UCB-MSCs (5.0 × 10 7 cells) could effectively reduce the symptom of AD and with little adverse effects and no relapse (29).…”
Section: The Clinical Efficacy Of Mscs and Their Derivatives Applied ...mentioning
confidence: 99%
See 1 more Smart Citation